Continuous Fabrication of Wide-Tip Microstructures for Bio-Inspired Dry Adhesives via Tip Inking Process - Sung Ho Lee; Cheol Woo Park; Moon Kyu Kwak (Journal of Chemistry)
In this paper, we report a new method for continuous fabrication of dry adhesives composed of microstructures with mushroom-shaped ends. Conventional mushroom microstructure fabrication is performed with a simple molding technique using a reversed phase master. In a typical fabrication process, thin- and wide-tip portions may be ripped during demolding, making it difficult to use in a continuous process. It is also difficult to apply the mushroom structure master to a continuous process system in roll form. Here, a continuous fabrication process was developed by applying the method of fabricating a wide tip using a tip inking method after forming a micropillar. Through the continuous process, the dry adhesive was successfully fabricated and the durability was measured with a reasonable pull-off strength (13 N/cm2). In addition to the reasonable adhesion, high durability is guaranteed, and fabricated dry adhesives are expected to be used in various fields.